Effects of Chitosan Concentration on the Protein Release Behaviour of Electrospun Poly(epsilon-caprolactone)/Chitosan Nanofibers - Roozbahani, Fatemeh (2015)
Poly(ε-caprolactone)/chitosan (PCL/chitosan) blend nanofibers with different ratios of chitosan were electrospun from a formic acid/acetic acid (FA/AA) solvent system. Bovine serum albumin (BSA) was used as a model protein to incorporate biochemical cues into the nanofibrous scaffolds. The morphological characteristics of PCL/chitosan and PCL/chitosan/BSA Nanofibers were investigated by scanning electron microscopy (SEM). Fourier transform infrared spectroscopy (FTIR) was used to detect the presence of polymeric ingredients and BSA in the Nanofibers. The effects of the polymer blend ratio and BSA concentration on the morphological characteristics and consequently on the BSA release pattern were evaluated. The average fiber diameter and pore size were greater in Nanofibers containing BSA. The chitosan ratio played a significant role in the BSA release profile from the PCL/chitosan/BSA blend. Nanofibrous scaffolds with higher chitosan ratios exhibited less intense bursts in the BSA release profile.